Association of Infant and Child Health Characteristics With the Hazard of Any Medical Condition or Disability in Australian Children - Ahmad, Kabir; Keramat, Syed Afroz; Sathi, Nusrat Jahan; Kabir, Enamul; Khanam, Rasheda (My University, 2022)
Background: The incidence of any medical condition (e.g., sight, hearing, and speech problems, blackouts, chronic pain etc.) or disability (e.g., limited use of arms or fingers, legs, and feet, or other physical long-term health condition limiting everyday activities etc.) have been increasing among Australian children in recent decades. Objectives: This study assessed whether infant or child health characteristics might be predictors of subsequent medical conditions or disabilities in children in the first 15 years of life. Methods: Using time to event data of 5107 children, obtained from the Birth cohort of the Longitudinal Study of Australian Children, the study estimated the incidence of any medical condition or disability using the survival analysis technique. This study followed up the children from birth to 14 or 15 years of age (2004 - 2018) and assessed the association of infant and child health characteristics (birthweight, gestational age, use of intensive care unit or ventilator during their neonatal age and obesity) with hazard of any medical condition or disability using the random effect parametric survival regression model. The infant characteristics were measured in the Wave 1 while the children were aged 0/1 year and obesity characteristics were measured longitudinally over all the waves up to 14/15 years of age. Results: The hazard rate of any medical condition or disability for all participants was 26.13 per 1000 person-years among children in Australia. This hazard incidence was higher among low birthweight (39.07) and obese (34.37) children and among those who had received after‑birth ventilation or intensive care unit emergency services (36.87). The parametric panel regression model also suggests that children with low birthweight were 1.43 times (Hazard Ratio: 1.43, 95% Confidence Interval: 1.05 - 1.94) more likely to have any medical condition or disability than children with normal birthweight. The time to event analyses also revealed that being recipient of after-birth emergencies (HR: 1.47, 95% CI: 1.23 - 1.75), being male children (HR: 1.30, 95% CI: 1.14 - 1.48) or being obese (HR: 1.38, 95% CI: 1.07 – 1.79) significantly increased the likelihood of the incidence of a medical condition or disability among children. The regression model was adjusted for region of residence, language spoken at home, indigenous status, whether the study child has both parents, mothers age at birth and education of mothers. Conclusions: This study predicts the risk factors of any medical condition or disability among Australian children. The study findings suggest that infants with low birth weight, hospital emergency service use and children with obesity would benefit from additional health care monitoring to minimize the risk of any medical condition or disability.
Research Square
Keywords: Health and wellbeing